2020
DOI: 10.1080/09546634.2020.1832649
|View full text |Cite
|
Sign up to set email alerts
|

Dermatologists on the medical need for therapeutic drug monitoring of biologics in psoriasis: results of a structured survey

Abstract: Background: Therapeutic drug monitoring (TDM) may lead to more rational use of biologics. Still, TDM is largely underexplored in psoriasis. Little is known about the dosing behavior of biologics by dermatologists, and their attitude towards TDM.Objective: Exploration of the awareness and need for the concept of TDM in psoriasis amongst (inter)national dermatologists. Method: A survey was distributed at the Belgian Dermatology Days 2019 and Skin Inflammation & Psoriasis International Network (SPIN) Congress 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 60 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…Real-life clinical cases of empirical dose adjustments of secukinumab and the lack of guidelines, highlight the existing unmet medical need to guide physicians in their clinical decision-making regarding treatment modifications. 34 TDM of biologics may pave the way towards personalized exposure-based dose optimization Figure 2 Goodness-of-fit plot of the response models. The probability of obtaining an optimal response [defined as (a) Psoriasis Area and Severity Index (PASI) ≤ 2, (b) 90% reduction in PASI compared with baseline or (c) PASI ≤ 2 or 90% reduction in PASI compared with baseline] is presented against the secukinumab trough concentrations (TCs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Real-life clinical cases of empirical dose adjustments of secukinumab and the lack of guidelines, highlight the existing unmet medical need to guide physicians in their clinical decision-making regarding treatment modifications. 34 TDM of biologics may pave the way towards personalized exposure-based dose optimization Figure 2 Goodness-of-fit plot of the response models. The probability of obtaining an optimal response [defined as (a) Psoriasis Area and Severity Index (PASI) ≤ 2, (b) 90% reduction in PASI compared with baseline or (c) PASI ≤ 2 or 90% reduction in PASI compared with baseline] is presented against the secukinumab trough concentrations (TCs).…”
Section: Discussionmentioning
confidence: 99%
“…Real‐life clinical cases of empirical dose adjustments of secukinumab and the lack of guidelines, highlight the existing unmet medical need to guide physicians in their clinical decision‐making regarding treatment modifications 34 . TDM of biologics may pave the way towards personalized exposure‐based dose optimization and its relevance is driven by the presence of a dose–response relationship 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, the data in favor of TDM in psoriasis are growing. Based on the distribution of a survey among dermatologists who participated in Belgian Dermatology Days 2019 and Skin Inflammation & Psoriasis International Network Congress 2019, Schots et al [ 121 ] indicated that 70% of the total study cohort admitted the need for TDM, implying the necessity in the daily dermatology routine for active interaction about the accessibility, utility, and application of TDM assays. However, over the years, there has been much confusion about what exposure metrics are informative in patients with psoriasis.…”
Section: Therapeutic Drug Monitoring Of Monoclonal Antibodies In Psor...mentioning
confidence: 99%
“…To date, several reviews have summarized the studies assessing the exposure-response relationships and optimal concentration thresholds for mAbs in inflammatory diseases [ 22 , 23 , 24 , 25 , 26 ]. It seems the consensus and guidelines for TDM and target mAb concentrations are best established in the field of Gastroenterology, but the advances are continuously made in the management of rheumatic and dermatologic conditions, as well ( Table 1 ) [ 23 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Therapeutic Drug Monitoring Of Monoclonal Antibodiesmentioning
confidence: 99%
“…To date, several reviews have summarized the studies assessing the exposure-response relationships and optimal concentration thresholds for mAbs in inflammatory diseases [22][23][24][25][26]. It seems the consensus and guidelines for TDM and target mAb concentrations are best established in the field of Gastroenterology, but the advances are continuously made in the management of rheumatic and dermatologic conditions, as well (Table 1) [23,[27][28][29][30][31][32][33]. TDM can be done reactively, as a consequence to a patient's nonresponse to treatment, or proactively, when the patient is in a state of remission and the main purpose of TDM is prophylactic [35,36].…”
Section: Therapeutic Drug Monitoring Of Monoclonal Antibodiesmentioning
confidence: 99%